DNTTIP1 is a Prognostic Biomarker Correlated With Immune Infiltrates in Hepatocellular Carcinoma: A Study Based on The Cancer Genome Atlas Data - Zhu, Changyu; Tong, Rongsheng; Jiang, Xiaolei; Xiao, Hua; Guan, Jianmei; Shu, Jianchen (Frontiers in Genetics, 2022)
Deoxynucleotidyltransferase terminal interacting protein 1 (DNTTIP1) is involved in the deacetylation of p53 in regulating cell-cycle and is associated with cancers at the molecular level. In this study, we evaluated prognostic value in hepatocellular carcinoma (HCC) based on data from The Cancer Genome Atlas (TCGA) database. Kurskal-Wallis test, Wilconxon signed-rank test, and logistic regression were used to evaluate the relationship between DNTTIP1 expression and clinical-pathologic features. Cox regression and the Kaplan-Meier method were adopted to evaluate prognosis-related factors. Gene set enrichment analysis (GSEA) was performed to identify the key pathways related to DNTTIP1. The correlations between DNTTIP1 and cancer immune infiltrates were investigated by single-sample Gene Set Enrichment Analysis (ssGSEA). DNTTIP1 was found to be up-regulated with amplification in tumor tissues in multiple HCC cohorts. High DNTTIP1 expression was associated with poorer overall survival (OS) and disease-free survival (DFS). GSEA suggested that DNTTIP1 regulates the cell cycle mitotic, G1/S and G2/M phase in the cell cycle, as well as Fc fragment of IgE receptor I (FCERI) mediated NF-κB and MAPK pathway, Fc fragment of IgG receptor (FCGR) activation pathways. Notably, ssGSEA indicated that DNTTIP1 expression was positively correlated with infiltrating levels of Th2 cells, Tfh, NK CD56 bright cells, aDCs, T helper cells, Th1 cells, and Macrophages. These findings suggest that DNTTIP1 is correlated with prognosis and immune infiltrating in HCC, which lays a foundation for further study of the immune regulatory role of DNTTIP1 in HCC.